2019
DOI: 10.1111/mcn.12834
|View full text |Cite
|
Sign up to set email alerts
|

The association of early linear growth and haemoglobin concentration with later cognitive, motor, and social–emotional development at preschool age in Ghana

Abstract: It is important to identify the periods during childhood when exposure to environmental risk factors results in long‐term neurodevelopmental deficits. Stunting and anaemia may be sensitive indicators of exposure to such risks. In a prospective cohort enrolled before birth, we investigated the association of developmental scores at 4–6 years with (a) birth length and linear growth during three postnatal periods and (2) haemoglobin (Hb) concentration at three time points. Children were participants in a follow‐u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 59 publications
0
11
1
1
Order By: Relevance
“…Cognitive development and linear growth at age 4–6 years was also reported by Ocansey et al . ( 25 ) to be significantly associated with haemoglobin concentration at 18 months but, unlike Mireku et al . ( 23 ) , Ocansey et al .…”
Section: Resultscontrasting
confidence: 64%
See 3 more Smart Citations
“…Cognitive development and linear growth at age 4–6 years was also reported by Ocansey et al . ( 25 ) to be significantly associated with haemoglobin concentration at 18 months but, unlike Mireku et al . ( 23 ) , Ocansey et al .…”
Section: Resultscontrasting
confidence: 64%
“…( 23 ) , Ocansey et al . ( 25 ) found no association with motor development. A randomised control trial (RCT) exploring prenatal supplementation with vitamin A and zinc ( 21 ) reported no developmental benefits in children of women consuming the supplement.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…The association between persistent stunting and cognitive development has been demonstrated [15]. A recent meta-analysis of 29 LMICs has established a positive association between linear growth and cognitive development in the first 2 years of life [16], but the meta-analysis could not integrate environmental, educational, and follow-up data to describe the relationship between stunting and cognitive impairment.…”
Section: Introductionmentioning
confidence: 99%